FAmily‐Led RehabiliTaTion aftEr Stroke in INDia: the ATTEND pilot study. Issue 4 (9th March 2015) - Pandian, Jeyaraj D.; Felix, Cynthia; Kaur, Paramdeep; Sharma, Deepika; Julia, Lizzie; Toor, Gagan; Arora, Rajni; Gandhi, Dorcas B.C.; Verma, Shweta J.; Anderson, Craig S.; Langhorne, Peter; Murthy, G.V.S.; et al.
<x xml:space="preserve">Abstract</x> Background The aim of this pilot study was to determine the feasibility of a multicenter, randomized, controlled trial in India of a family‐led, trained caregiver‐delivered, home‐based rehabilitation intervention vs. routine care. Methods A prospective, randomized (within seven‐days of hospital admission), blinded outcome assessor, controlled trial of structured home‐based rehabilitation delivered by trained and protocol‐guided family caregivers (intervention) vs. routine care alone (control) was conducted in patients with residual disability. Key feasibility measures were recruitment, acceptance and adherence to assessment procedures, and follow‐up of participants over six‐months. CTRI/2014/10/005133. Results A total of 104 patients from the stroke unit at Christian Medical College, Ludhiana were recruited over nine‐months. Recruitment was feasible and accepted by patients and their carers. Important observations were made regarding potential unblinding of the participants, contamination of therapy between the randomized groups, organization of home visits, and resources required for a multicenter study. Conclusion The pilot study established the feasibility of conducting a large‐scale study of family‐led, trained caregiver‐delivered, home‐based stroke rehabilitation in a low resource setting. The main phase of the trial 'ATTEND' is currently underway in over 10 centers in India.